Cost of Serving Others: A Moderated Mediation Model of OCB, Ego Depletion, and Service Sabotage - Hongbo, Li; Waqas, Muhammad; Tariq, Hussain; Yahya, Farzan; Marfoh, Joseph; Ali, Ahsan; Ali, Syed Muhammad (Frontiers in Psychology, 2021)
Taking support from ego-depletion theory, this study examines ego depletion as a mechanism that explains how employees’ organizational citizenship behavior (OCB) leads to antagonistic consequences, i.e., service sabotage. Employees’ positive psychological capital (PsyCap) is considered a moderator. PROCESS macro was used to test all the hypotheses using time-lagged, dyadic data collected from 420 employees and their 112 their supervisors associated with the service industry in China. This study finds that employees’ exhibition of OCB is positively linked to ego depletion, which in turn drives service sabotage behavior. Furthermore, employees’ PsyCap weakens the effect of OCB on employees’ ego depletion. This study highlights the dark side of OCB, the mechanism through which it causes adverse effects, and the moderating effect of PsyCap. It also provides insights to the organizations for managing service sector employees to effectively interact with customers.